Gordis epidemiology - Celentano, David D.; Szklo, M. (Moyses); Farag, Youssef M. K.; Gordis, Leon, 1934-2015. (Philadelphia, PA : Elsevier, 2025)
Continuing in the tradition of award-winning educator and epidemiologist Dr. Leon Gordis, Gordis Epidemiology, 7th Edition, provides a solid introduction to basic epidemiologic principles as well as practical applications in public health and clinical practice, highlighted by real-world examples throughout. Written by Drs. David D Celentano, Moyses Szklo, and Youssef Farag of Johns Hopkins University, this bestselling text is known for its reader-friendly, accessible writing style and practical approach to a complex and challenging subject, making it a favorite text of students as well as an ideal resource for health care providers, health policy makers, and epidemiologists at all levels of training and practice.
The epidemiologic approach to disease and intervention -- Using epidemiology to identify the cause of disease -- Applying epidemiology to evaluation and policy.
"The first printing of ... Chapter 4 includes some misplaced text"--Slip laid in. Corrected text available for download.
Includes bibliographical references and index.
Catalography
Keywords: Epidemiology; Epidemiologic Methods